PROFESSOR AHMAD FARHAN APPOINTED AS NEW USM DVC (ACADEMIC AND INTERNATIONAL) - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
Professor Dr. Ahmad Farhan Mohd. Sadullah, 50, whose expertise is in the field of Transport Engineering, has been appointed as the new Universiti Sains Malaysia (USM) Deputy ViceChancellor (Academic and International) effective 15 March 2017 for a threeyear term.